2011
DOI: 10.1186/1556-276x-6-218
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition on the Si(001) clean surface prepared in UHV MBE chamber: a study by high-resolution STM and in situ RHEED

Abstract: The Si(001) surface deoxidized by short annealing at T ~ 925°C in the ultrahigh vacuum molecuar beam epitaxy chamber has been in situ investigated using high-resolution scanning tunneling microscopy (STM)and redegreesected high-energy electron diffraction (RHEED. RHEED patterns corresponding to (2 × 1) and (4 × 4) structures were observed during sample treatment. The (4 × 4) reconstruction arose at T ≲ 600°C after annealing. The reconstruction was observed to be reversible: the (4 × 4) structure turned into th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…At first, they were washed in the ammonia-peroxide solution and dried in the isopropyl alcohol vapor (for 10 min) and the clean air. Additionally, before moving into the MBE chamber, the substrates were annealed at 600°C at the residual gas pressure of less than 5 × 10 −9 Torr in the preliminary annealing chamber for 6 hours [1,2,23,27].…”
Section: Samplesmentioning
confidence: 99%
“…At first, they were washed in the ammonia-peroxide solution and dried in the isopropyl alcohol vapor (for 10 min) and the clean air. Additionally, before moving into the MBE chamber, the substrates were annealed at 600°C at the residual gas pressure of less than 5 × 10 −9 Torr in the preliminary annealing chamber for 6 hours [1,2,23,27].…”
Section: Samplesmentioning
confidence: 99%
“…The Ge/Si samples were grown and characterized using an integrated ultrahigh vacuum instrument [9][10][11][12] built on the basis of the Riber SSC 2 surface science center with the EVA 32 molecular-beam epitaxy (MBE) chamber equipped with the RH20 reflection high-energy electron diffraction (RHEED) tool (Staib Instruments) and connected through a transfer line to the GPI-300 ultrahigh vacuum scanning tunnelling microscope (STM) [13][14][15]. Sources with the electron beam evaporation were used for Ge or Si deposition.…”
Section: Equipment and Techniquesmentioning
confidence: 99%
“…Then, the temperature was rapidly lowered to about 750℃. The rate of the further cooling was around 0.4℃/s that corresponded to the 'quenching' mode applied in [10].…”
Section: Sample Preparation Procedures Preparation Of Samples For Stmmentioning
confidence: 99%
“…The experiments were carried out using an ultrahigh-vacuum (UHV) MBE chamber (Riber EVA 32) connected with a UHV scanning tunnelling microscope (STM) chamber (GPI 300) [7,13,14]. The rates of Ge and Si deposition and the coverages of Ge and Si (h Ge , h Si ) were measured by a graduated in advance film thickness monitors (Inficon Leybold-Heraeus XTC 751-001-G1) with quartz sensors installed in the MBE chamber.…”
Section: Techniques and Equipmentmentioning
confidence: 99%
“…Ge oval drops with the lateral dimensions of about a hundred nanometers have the highest number density among the detected clusters. Then, we detected a mixture of c(4×2) and p(2×2) reconstructions on the surface of the formed wetting layer whereas the simultaneous presence of both these structures in comparable proportions on wetting layer patches is a distinctive feature of the low-temperature mode of the wetting layer growth (at T gr < 600 ℃) in the MBE process [6,7]. And finally, we have shown that the Ge drops disappear from the surface as a result of long-term isothermal annealing of the original Ge film under the conditions of an isolated system; the sizes of the large clusters increase at the expense of the smaller ones and the total density of Ge clusters on the surface decreases by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 96%